Plus disease in retinopathy of prematurity: diagnostic impact of field of view - Rao, Rohini (2012)
PURPOSE: To examine the impact of retinal field of view and magnification on inter-expert reliability of plus disease diagnosis in retinopathy of prematurity (ROP). METHODS: 15 wide-angle images from infants with ROP were cropped and adjusted in magnification to create two additional image categories: medium-angle (40–50°) and narrow-angle (20–30°). These 45 images were uploaded to a web-based system and interpreted independently by 13 ROP experts using a 3-level (plus, pre-plus, neither) and 2-level (plus, not plus) classification. Absolute agreement and kappa statistics were calculated to compare inter-expert reliability. RESULTS: In the 3-level classification, ≥70% experts agreed on the same diagnosis in 8/15 (53%) wide-angle images, but only in 3/15 (20%) medium-angle and 3/15 (20%) narrow-angle images. In the 2-level classification, ≥80% experts agreed on the same diagnosis in 11/15 (73%) wide-angle images, but only in 9/15 (60%) medium-angle and 3/15 (20%) narrow angle images. Mean kappa of each expert compared to all other experts was 0.40–0.59 in 8/13 (62%) experts using wide-angle images, was 0–0.19 in 7/13 (54%) experts using medium-angle images, and was 0.20–0.39 in 9/13 (69%) experts using narrow-angle images. CONCLUSIONS: Inter-expert agreement in plus disease diagnosis in wide-angle images is higher than from medium-angle and narrow-angle images. Plus disease is defined using a narrow-angle standard published photograph, yet this study suggests that peripheral findings also contribute to diagnosis.